(untitled) (London Journal of Engineering Research, 2025)
In this article, the design, construction and control of a two-wheeled balancing robot was carried out with two PID controllers and fuzzy logic. This type of robot has advantages such as lower energy consumption and the ability to be used in small spaces with the ability to navigate in the entire workspace and rotate in place compared to other wheeled robots. Therefore, the need for research on the knowledge of building a two-wheeled balancing robot and controlling its balance optimally is felt to enter fields such as medical robots (assistant and military and robotics of humanoid robots), etc. For the design and modeling of the robot, SolidWorks software was used, and for programming, Arduino software was used along with the Arduino microcontroller board. In this research, the robot system is nonlinear and is considered as a black box, and two linear PID and nonlinear fuzzy controllers have been used. After conducting investigations and obtaining numerous results for both controllers in the results section, the performance of the fuzzy controller was observed to be much more optimal than the PID controller. The PID coefficients have been obtained experimentally, and the membership functions of the fuzzy controller have also been adjusted experimentally, and the Mamdani method and trapezoidal functions have been used. All the results have been obtained from the Arduino software and with a serial port connection between the computer and the Arduino microcontroller, all of which are presented in the results section.